The roles of case managers and problems encountered in implementing patient centered care in hospitals - Ni Kadek Yuliati; Ni Made Sri Nopiyani; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2019)
Background and purpose: Patient centered care in hospitals has yet to be well implemented. The role of case managers is very important in the implementation of patient centered care in hospitals. Research publications on the role of case managers in patient centered care in Indonesia remain limited. This study aims to explore the roles of case managers and problems encountered in the implementation of patient centered care in hospitals. Methods: This study used a qualitative design with a case study approach conducted at Bangli District Hospital in Bali in April 2019. Data was collected through in-depth interviews with seventeen purposively selected informants consisting of ten case managers, one deputy director of medical services, two patient’s family members, two specialist doctors and two implementing nurses at Bangli District Hospital. This study uses the Patient Centered Care Framework from Greene which consists of three dimensions in patient centered care namely interpersonal, clinical and structural dimensions. Data was analyzed thematically using deductive and inductive techniques. Data validation was conducted through triangulation of data based on different sources, member checking and peer debriefing. Results: In this study, five main themes were found regarding the role of case managers in the implementation of patient centered care in hospitals, namely interpersonal, clinical and structural dimensions, support and expectations of case managers. The identified role of the case manager in the interpersonal dimension consisted of listening to patients and families actively, coordination and collaboration in problem solving, providing accurate and easy to understand information about care. Problems encountered included lack of communication between the service provider components and between the service provider with patients and their families. Roles of case manager in the clinical dimension are to hold meetings with a professional team of care givers and continuous monitoring of services to patients, while the issue encountered is the mismatch of time of service provision by specialist doctors. Roles of case managers in the structural dimension is coordination with policy holders, use of information technology and patient reporting. Problems encountered were inappropriate recruitment of case managers, lack of training of case managers, incomplete facilities, inconvenience of services and inadequate incentives. Supports from hospitals for case managers were support of facilities and legality as case managers. Expectations of case managers include case manager training, rewarding and career development opportunities. Conclusion: The roles of case managers in implementing patient centered care in Bangli District Hospital are not optimal. Efforts to address issues in the interpersonal, clinical and structural dimensions need to be carried out by the hospital management to enhance the role of case managers in the implementation of patient centered care.